The Modern Double-Poling Technique Is Not More Energy Efficient Than the Old-Fashioned Double-Poling Technique at a Submaximal Work Intensity - Carlsson, Tomas; Fjordell, Wilma; Wedholm, Lars; Swarén, Mikael; Carlsson, Magnus (Frontiers in Sports and Active Living, 2022)
The purpose of the study was to investigate whether there are energy-efficiency differences between the execution of the old-fashioned double-poling technique (DPOLD) and the modern double-poling technique (DPMOD) at a submaximal work intensity among elite male cross-country skiers. Fifteen elite male cross-country skiers completed two 4-min tests at a constant mechanical work rate (MWR) using the DPMOD and DPOLD. During the last minute of each test, the mean oxygen uptake (VO2) and respiratory exchange ratio (RER) were analyzed, from which the metabolic rate (MR) and gross efficiency (GE) were calculated. In addition, the difference between pretest and posttest blood-lactate concentrations (BLadiff) was determined. For each technique, skiers' joint angles (i.e., heel, ankle, knee, hip, shoulder, and elbow) were analyzed at the highest and lowest positions during the double-poling cycle. Paired-samples t-tests were used to investigate differences between DPMOD and DPOLD outcomes. There were no significant differences in either VO2mean, MR, GE, or BLadiff (all P > 0.05) between the DPMOD and DPOLD tests. DPMOD execution was associated with a higher RER (P < 0.05). Significant technique-specific differences were found in either the highest and/or the lowest position for all six analyzed joint angles (all P < 0.001). Hence, despite decades of double-poling technique development, which is reflected in the significant biomechanical differences between DPOLD and DPMOD execution, at submaximal work intensity, the modern technique is not more energy efficient than the old-fashioned technique.